A study of the critical chain project management method applied to a multiproject system - Ordoñez, Robert Eduardo Cooper (2019)
In 1997, Eliyahu Goldratt proposed a method called Critical Chain Project Management (CCPM) to minimize the inefficiencies identified in traditional project management. The project management community accepted the proposed method as a viable alternative. However, to allow its implementation with a multiproject system, more research was necessary. Seeking to identify the key factors that influence the performance of the multiproject system applying the CCPM method, we performed a case study. Logistic regression analysis showed that applying the CCPM method in a multiproject system allows for better time estimation of activities and facilitates the allocation of critical resources.